Ontologi Penelitian Hukum Islam Berbasis Paradigma Guba dan Lincoln - Muhammad Helmi (Jurnal Hukum Islam, 2020)
This paper aims to analyze and develop Islamic law research by using paradigms of Guba and Lincoln. This literature study uses a philosophical approach. The results of the study showed that the development of normative and empirical Islamic law research based on the paradigms of Guba and Lincoln is adjusted to the fundamental beliefs of researchers which are recognized based on ontology questions, namely 1) if the researchers’ basic beliefs to understand rules based on “what is it” and “what is written” or textually, it is called positivism paradigm; 2) if the basic beliefs of the researchers in understanding rules of contextual Islamic law, it is included post-positivism paradigm; 3) if the researchers change the false understanding about rules, it is called critical theory paradigm; 4) if the basic beliefs of researchers are obtained from diverse thoughts, then it includes constructive paradigm. These a variety of paradigms will bring about the researchers to answer the problems in the implementation and development of Islamic law research. Therefore, the researchers of Islamic law should develop their researches through these various paradigms from the beginning to the end, so that the paradigms will lead to answering the research problems of contemporary Islamic law.